The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18203/2349-3291.ijcp20194709
|View full text |Cite
|
Sign up to set email alerts
|

Survey of obesity among school children in rural Kerala, India

Abstract: Background: Childhood obesity is a risk factor for subsequent development of diabetes mellitus, hypertension etc. Rural children show lower levels of obesity and higher rates of malnutrion. Objectives: Study seeks to access the prevalence of obesity and overweight among higher secondary students in rural Kerala).Methods: 1577 students were selected from schools picked randomly in and around vadavukode block in Ernakulam district, Kerala, of which 761 from private and 816 from government and aided school. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…A higher prevalence of overweight/obesity similar to the present study findings were reported by Jagadesan S et al (private school-26.4%, government schools-4.6%) [14], and Tharkar S et al (12.1% among the children and 15.5 % among the adolescents) [15]. But a comparatively lower prevalence were reported by Viswambharan KJ [16], (7.7% were overweight or obese, 1.9% were obese and 5.8% were overweight, 8.2% among boys and 7.3% among girls) Cherian AT [17], Obesity 3.0% for boys and 5.3% for girls) and Abraham RJ [18] (overweight 7.4% and obesity 2.5%).…”
Section: Discussionmentioning
confidence: 92%
“…A higher prevalence of overweight/obesity similar to the present study findings were reported by Jagadesan S et al (private school-26.4%, government schools-4.6%) [14], and Tharkar S et al (12.1% among the children and 15.5 % among the adolescents) [15]. But a comparatively lower prevalence were reported by Viswambharan KJ [16], (7.7% were overweight or obese, 1.9% were obese and 5.8% were overweight, 8.2% among boys and 7.3% among girls) Cherian AT [17], Obesity 3.0% for boys and 5.3% for girls) and Abraham RJ [18] (overweight 7.4% and obesity 2.5%).…”
Section: Discussionmentioning
confidence: 92%
“…In spite of a well-planned curriculum and provision in school timetable, Physical and Health Education has been mostly neglected in the schools in the state of Kerala. This has resulted in an unprecedented hike in the percentage of obese and overweight children and adolescents, with current estimates at approximately 10% in Kerala (Nair & Chellappan, 2021; Viswambharan, Bina & Raphael, 2020; Abraham & Pillai, 2019) [7,13,1] . Decreased physical activity has been identified as a main cause of obesity in children and adolescents (Sallis et al, 2012) [10] .…”
Section: Introductionmentioning
confidence: 99%